Knowledge, Attitude and Prevention Practice Among the Volunteers (HCPS) in Implementing 5M - Julia Christy Labetubun; Dian Ayubi; Tri Krianto (Publikasi Indonesia, 2022)
Health care providers (HCP) are a group that has a high risk of being exposed to COVID-19. Due to the large number of personnel needed to handle COVID-19, in several hospitals, health volunteers were involved to assist in the treatment process. As workers who deal directly with COVID-19 patients, volunteers are the targets in this study. HCP's health behavior can influence the escalation of prevention and control cases at their level. Therefore, this study aims to examine the practice of knowledge, attitudes, prevention (KAP) and factors related to the application of 5M on volunteers (HCP) at Hospital